Sposób zachowania się pacjenta jako przyczyna uzasadniająca realizację prawa lekarza do odmowy leczenia - Zoń, Katarzyna Maria (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
A doctor has a fundamental duty to provide health services, which also includes treatment of a patient. This obligation is not absolute. First the statutory Art. 38 of the Act of 5 December 1996 on the medical and dental professions and deontology regulations Art. 7 of the Medical Code of Ethics related to this topic should be explained, because it is necessary for further consideration. According to the above-mentioned provision a doctor has a right to refuse treatment of a patient.The aim of this paper is to analyze the issue of a doctor’s right to refuse treatment for reasons attributable to the patient and related to the patient’s conduct. In this context it should be highlighted that a doctor can exercise the above right under certain circumstances. The most essential is the significant restriction to make use of a right to refuse treatment. All strictly formulated terms require cumulative fulfilment. This special regulation ensures in an appropriate way respect for the rights and interests of patients.To sum up, a legitimate reason to exercise a doctor’s right to refuse treatment is also the patient’s behavior, such as aggressive conduct, multiple non-compliance with the doctor’s order or negating the competence of the doctor. This thesis finds support both in statutory and deontology regulations.
Keywords: odmowa leczenia; prawa lekarza; prawa pacjenta; relacje lekarz-pacjent; zachowanie pacjenta